REVIEW METODE DEODORISASI PADA MINYAK IKAN - Rhinard Valery Goethe Randang; Pande Made Nova Armita Sari (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2023)
Fish oil has a lot of potential for humans. However, this potential is obstructed by the fishy smell. Therefore, deodorization is carried out to overcome this problem. This article is a literature review that aims to review several methods that are commonly used in fish oil deodorization. The method in preparing this article was carried out by searching the Google Scholar and PubChem databases. The search results show that in general there are three types of methods in fish oil deodorization namely physical methods, chemical methods, and biological methods. The three methods have their own advantages and disadvantages, so before deodorizing it is necessary to know the purpose of the deodorization being carried out. Optimization of the combination method is needed to increase the value of fish oil and its processed products.